MODIS Collection 6 Land Product Subsets Web Service - ORNL DAAC (ORNL Distributed Active Archive Center, 2017)
The MODIS Web Service provides data access capabilities for Moderate Resolution Imaging Spectroradiometer (MODIS) Collection 6 land products. The web service provides data access functions for users to execute on their local computing resources. The MODIS Web Service is built upon the ORNL DAAC's MODIS Global Subsetting and Visualization Tool that provides customized subsets and visualization of MODIS land products for any land location on earth. With the web service users can retrieve land product subsets through command line operations; download subsets directly into applications such as Python, R, Perl, Matlab, and others and integrate the subsets into client side workflows; download subsets and write custom code to use the subsets in a visualization; and download subsets and write custom code for data reformatting.